The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/smartcities2040032
|View full text |Cite
|
Sign up to set email alerts
|

Urban Systems Design: A Conceptual Framework for Planning Smart Communities

Abstract: Urban systems design arises from disparate current planning approaches (urban design, Planning Support Systems, and community engagement), compounded by the reemergence of rational planning methods from new technology (Internet of Things (IoT), metric based analysis, and big data). The proposed methods join social considerations (Human Well-Being), environmental needs (Sustainability), climate change and disaster mitigation (Resilience), and prosperity (Economics) as the four foundational pillars. Urban system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Ref. [24] focused on the impacts of design on changing urban systems and proposed a framework for the planning and designing of public projects. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [24] focused on the impacts of design on changing urban systems and proposed a framework for the planning and designing of public projects. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It indicates that life course events do not always lead to a change in car ownership. The costs (time, money, and convenience) of changing car ownership in general make respondents reluctant to choose a sustainable mobility tool [33][34][35][36]. As for the choice of the mobility tool, people prefer a conventional car over an EV, in case they replace the current car or purchase an additional car.…”
Section: Attributes Of Alternativesmentioning
confidence: 99%
“…As mentioned previously, technological development has motivated the formulation of smart cities. Although this concept is based on the development of information and communications technology (ICT) and the internet of things (IoT), it also influences the physical perspective of urban development, such as zones, infrastructure allocations, and urban transport networks [11,15]. It is noted that universal agreement on a specific definition of a "smart city" is still lacking at present, and its primary field is in the usage of ICT and IoT in the sectors of infrastructure, buildings, and energy [84].…”
Section: Exogenous Trends: Urban Developmentmentioning
confidence: 99%
“…Freudendal-Pedersen et al (2019) [14] discussed the impacts of mobility on smart cities, particularly on the aspects of automation and sustainability. Tobey et al (2019) [15] demonstrated a conceptual framework for planning smart communities to take account of sustainable transport, which employed an iterative three-phase development loop. Hammad et al (2019) [11] proposed a mathematical optimization framework to optimize zoning, land-use allocation, the location of novel constructions, and investment decision-making related to infrastructure projects in smart cities.…”
Section: Introductionmentioning
confidence: 99%